Characteristics of Soil Fauna Communities and Habitat in Small- Holder Cocoa Plantation in South Konawe - Laode Muhammad Harjoni Kilowasid; Tati Suryati Syamsudin; Franciscus Xaverius Susilo; Endah Sulistyawati; Hasbullah Syaf (JOURNAL OF TROPICAL SOILS, 2013)
The composition of the soil fauna community have played an important role in regulating decomposition and nutrient cycling in agro-ecosystems (include cocoa plantation). Changes in food availability and conditions in the soil habitat can affected the abundance and diversity of soil fauna. This study aimed: (i) to analyze the pattern of changes in soil fauna community composition and characteristic of soil habitat based on the age increasing of cocoa plantation, and (ii) to identify taxa of soil fauna and factors of soil habitat which differentiate among the cocoa plantations. Sampling of soil, roots and soil fauna was conducted from cocoa plantation aged 4, 5, 7, 10, and 16years. Difference in composition of the soil fauna community between ages of the cocoa plantation is significant. Profile of soil habitats was differ significantly between the cocoa plantations, except 5 and 7 years aged. A group of soil fauna has relatively limited in its movement, and sensitively to changes in temperature, soil acidity, and the availability of food and nitrogen are taxa differentiating between soil fauna communities. Soil physic-chemical conditions that affect metabolic activity, movement, and the availability of food for soil fauna is a  distinguishing factor of the characteristics of the soil habitat between different ages of smallholder cocoa plantations.Keywords: Abundance, arthropod, composition, nematodes[How to Cite: Kilowasid LMH, TS Syamsudin, F X Susilo, E Sulistyawati and H Syaf. 2013.Characteristics of Soil Fauna Communities and Habitat in Small-Holder Cocoa Plantation in South Konawe. J Trop Soils 18 (2): 149-159. Doi: 10.5400/jts.2013.18.2.149][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.149]REFERENCESAdejuyigbe CO, G Tian and GO Adeoye.1999. Soil microarthropod populations under natural and planted fallows in Southwestern Nigeria. Agroforest Sys 47: 263-272.Adl SM. 2008. Enchytraeids. In: Carter MR and Gregorich EG (eds.) Soil Sampling and Methods of Analysis. Canadian Society of Soil Science. pp. 445-453. Aeckerman IL, R Costantio, HG Gauch, J Lehman, SJ Riha and ECM Fernandes. 2009. Termite (insecta: isoptera) species composition in a primary rain forest and agroforests in Central Amazonia. Biotropica 41: 226-233. Allen AP, JF Gillooly and JH Brown. 2005. Linking the global cycle to individual metabolism. Func Ecol 19: 202-213.Bardgett R. 2005. The biology of soil: A community and ecosystem approach, Oxford University Press Inc., New York. 242p. Beisel JN, P Usseglio-Polatera, V Bachmann and JC Moreteau. 2003. A comparative analysis of evennes index sensitivity. Inte Rev Hydrobiol 88: 3-15. Belay-Tedla A, X Zhou, B Su, S Wan and Y Lou. 2009. Labile, recalcitrant, and microbial carbon and nitrogen pools of tallgrass prairie soils in the US Great Plains subjected to experimental warming and clipping. Soil Biol Biochem 41: 110-116.Blagodatsky S and P Smith. 2012. Soil physics meet soil biology: towards better mechanistic prediction of greenhouse gas emissions from soil. Soil Biol Biochem 47: 78-92.Bloem J, G Lebbink, KB Zwart, LA Bouwman, SLGE Burgers, JA de Vos and PC de Ruiter .1994. Dynamics of microorganisms, microbivores and nitrogen mineralization in winter wheat fields under conventional and integrated management. Agric Ecosys Environ 51: 129-143.Bloemers GF, M Hodda, PJD Lambshead, JH Lawton and FR Wanless. 1997. The effects of forest disturbance on diversity of tropical soil nematodes. Oecologia 111: 575-582.Bongers T and H Ferris. 1999. Nematode community structure as a bioindicator in environmental monitoring. TREE 14: 224-228.Bos MM, P Höhn, Shahabuddin, B Biiche, B Damayanti, I Steffan-Dewenter and T Tscharntke. 2007.  Insect diversity responses to forest conversion and agroforestry management. In: Tscharntke T, Leuschner C, Zeller M, Guhardja E, and Bidin A (eds.) The Stability of Tropical Rainforest Margins, Linking Ecological, Economic, and Social Constraints of Land Use and Conservation. Springer Verlag, Berlin, pp. 279-296.Camargo JA. 2008. Revisiting the relation between species diversity and information theory. Acta Biotheor 56: 275-283. Christensen KA. 1990. Insecta collembolan. In: DL Dindal (ed) Soil Biology Guide. John Willey & Sons, Singapore, pp. 965-995.Directorate General of Esatate, Agricultural Ministry, RI. 2012. Area and Production by Category of Producers. http://ditjenbun.deptan.go.id/cigraph/index.php/viewstat/komoditiutama/4-Kakao. Accessed on 6 June 2012.Delabie JHC, B Jahyny, IC do Nascimento, CSF Mariano, S Lacau, S Campiolo, SM Philpott and M Leponce. 2007. Contribution of cocoa plantations to the conservation of native ants (Insecta: Hymenoptera: Formicidae) with a special emphasis on the Atlantic forest fauna of Southern Bahia, Brazil. Biodivers Conserv 16: 2359-2384.Doran JW, MR Zeiss. 2000. Soil health and sustainability: managing the biotic component of soil quality. Appl Soil Ecol 15: 3-11.Evizal R, Tohari, ID Prijambada, J Widada and D Widianto. 2012. Soil bacterial diversity and productivity of coffe-shade tree agro-ecosystem. J Trop Soils 17: 181-187.Forge TA and J Kimpinski. 2008. Nematodes. In: MR Carter and EG Gregorich (eds). Soil Sampling and Methods of Analysis. Canadian Society of Soil Science, pp. 415-425.Gerson U, RL Smilet and R Ochoa. 2003. Mites (acari) for pest control. Blackwell Science, UK. Hairiah K, H Sulistyani, D Suprayogo, Widianto, P Purnomosidhi, RH Widodo and M van Noordwijk. 2006. Litter layer residence time in forest and coffee agroforestry systems in Sumberjaya, West Lampung. For Ecol Manage 224: 45-57.Hanel L. 2001. Succession of soil nematodes in pine forests on coal-mining sands near Cottbus, Germany. Appl Soil Ecol 16: 23 -34.Hopkins DW and RW Grogorich. 2005. Carbon as a subtrate for soil organisms. In: RD Bardgett,  MB Usher and DW Hopkins (eds). Biological diversity and function in soils. Cambridge University Press, New York, pp. 57-83.Hemmsbergen DA, MP Berg, M Loreau, JR van Hal, JH Faber and HA Verhoef. 2004. Biodiversity effects on soil processes explained by interspecific functional dissimilarity. Science 306: 1019-1020.   Hunt HW and DH Wall. 2002. Modelling the effects of loss of soil biodiversity on ecosystem function. Global Change Biol 8: 33-50.Isaac ME, AM Gordon, N Thevathasan, SK Oppong and J Quashie-Sam. 2005. Temporal changes in soil carbon and nitrogen in West African multistrata agroforestry systems: a chronosequence of pools and fluxes. Agroforest Systs 65: 23-31.Kardol P, TM Bezemer, A van der Wal and WH van der Putten. 2005. Successional trajectories of soil nematode and plant communities in a chronosequence of ex-arable lands. Biol  Conserv  126: 317-327.Kasprzak K. 1993. Methods for fixing and preserving soil animals. In: M Górny and L Grüm (eds). Methods in Soil Zoology. Elsevier, Amsterdam, pp.321-345.Kibblewhite MG, K Ritz and MJ Swift. 2008. Soil health in agricultural systems. Phil Trans R Soc B 363: 685-701.Kilowasid LMH, TS Syamsudin, FX Susilo and E Sulistyawati. 2012. Ecological diversity of soil fauna as ecosystem engineers in small-holder cocoa plantation in South Konawe. J Trop Soils 17: 173-180.  Kummerow J, Kummerow M and WS Da Silva. 1982. Fine-root growth dynamics in cacao (Theobroma cacao). Plant Soil 65: 193-201.Korhonen L, KT Korhonen, P Stenberg, M Maltamo and M Rautiainen. 2007. Local models for forest canopy cover with beta regression, Silva Fennica 4: 671-685.Lavelle P and AV Spain. 2001.  Soil ecology. Kluwer Academic Publisher, New York.Lawton JH, DE Bignell, GF Bloemers, P Eggleton and ME Hodda. 1996. Carbon flux and diversity of nematodes and termites in Cameroon forest soils. Biodiver Conserv 5: 261-273.Lukac M and DL Godbold. 2011. Soil Ecology in Northern Forests: a Belowground View of a Changing World. Cambridge Univerasity Press, New York.Marhaning AR, AAS Mills and SM Adl. 2009. Soil community changes during secondary succession to naturalized grasslands. Appl Soil Ecol 41: 137-147.Meserve PL, DA Kelt, B Milstead and JR Guitierrez. 2003. Thirteen years of shifting top-down and bottom-up control. BioScience  53: 633-646.Moco MKS, EF Gama-Rodrigues, AC Gama-Rodrigues, RCR Machado, and VC Baligar. 2009. Soil and litter fauna of cocoa agroforestry systems in Bahia, Brazil. Agroforest Syst 76: 127-138.  Moco MKS, EF Gama-Rodrigues, AC Gama-Rodrigues, RCR Machado and VC Baligar. 2010. Relationship between invertebrate communities, litter quality and soil attributes under different cacao agroforestry systems in the South of Bahia, Brazil. Appl Soil Ecol 46: 347-354.  Munoz F and J Beer. 2001. Fine root dynamics of shaded cacao plantations in Costa Rica. Agroforest Syst 51: 119-130.Nielsen UL. E. Ayres, D.H Wall and R.D Bardgett. 2010. Soil biodiversity and carbon cycling: a review and synthesis of studies examining diversity–function relationships. Eur J Soil Sci 62: 105-116.Panesar TS and VG Marshall. 2005. Monograph of soil nematodes from Coastal Douglas-Fir Forests in British Columbia. Royal Roads University, Canada. Available at: http://www.royalroads.net/nematodes. Peck SL, B Macquaid and CL Campbell. 1998. Using ant species (Hymenoptera: Formicidae) as a biological indicator of Agroecosystem condition. Environ Entomol 27: 1102-1110.Pradhan GB and MC Dash. 1987. Distribution and population dynamics of soil nematodes in a tropical forest ecosystem from Sambalpur, India. Proc Indian Acad Sci (Anim Sci) 96: 395-402.Rovira P and VR Vallejo. 2002. Labile and recalcitrant pool of carbon and nitrogen in organic matter decomposing at different depth in soil: an acid hydrolysis approach. Geoderma 107: 109-141.Ruf A, L Beck, P Dreher, K Hund-Rinke, J Römbke and J Spelda. 2003. A biological classification concept for the assessment for soil quality:”biological soil classification scheme” (BBSK), Agric Ecosyst Environ 98: 260-271.Saha S. 2010. Soil functions and diversity in organic and conventional farming. In: Lichtfouse E (eds). Sosiology, organic farming, climate change and soil science. Sustainable Agriculture Review 3, Springer Sciene + BussinesMedia B.V. pp. 275-301. Sanchez-Moreno S, S Smukler, H Ferris, AT O’Geen and LE Jackson. 2008. Nematode diversity, food web condition, and chemical and physical properties in different soil habitats of an organic farm. Biol Fertil Soils 44: 727-744.Sileshi G and PL Mafongoya. 2007. Quantity and quality of organic inputs from coppicing leguminous trees influence abundance of soil macrofauna in maize crops in eastern Zambia, Biol Fertil Soils  43: 333-340.Shahabuddin. 2010. Diversity and community structure of dung beetles (Coleoptera: Scarabaeidae) across a habitat disturbance gradient in Lore Lindu National Park, Central Sulawesi. Biodiversitas 11: 29-33. Schinner F, R Öhlinger, E Kandeler and K Margesin. 1996. Methods in soil biology. Springer, Berlin. 426p.  Sharma G, R Sharma and E Sharma. 2009. Impact of stand age on soil C, N and P dynamics in a 40-year chronosequence of alder-cardamom agroforestry atands of the Sikkim Himalaya, Pedobiologia. doi:10.1016/j.pedobi.2009.01.003.Sharon R, D Degani and M Warburg. 2001. Comparing the Soil macro-fauna in two oak-wood forests: does community structure differ under similar ambient conditions. Pedobiologia 45: 355-366.Smiley GL and J Kroschel. 2008. Temporal change in carbon stock of cocoa-gliricidia agroforest in Central Sulawesi, Indonesia. Agroforest Syst 73:  219-231. Smiley GL and J Kroschel. 2010. Yield development and nutrient dynamics in cocoa-gliricidia agroforest of Central Sulawesi, Indonesia. Agroforest Syst 78:  97-144.Susilo FX, AM Neutel, M van Noordwijk, K Hairiah, G Brown and MJ Swift. 2004. Soil biodiversity and food webs. In: M van Noordwijk, G Cadisch and CK Ong. Below-Ground Interactions in Tropical Agroecosystems: Concept and Models with Multiple Plant Components, CAB International Publishing, pp. 285-308.Syaf H. 2010. Analisis sumberdaya lahan tanaman kakao di Kabupaten Kolaka Provinsi Sulawesi Tenggara [Disertasi]. Universitas Padjajaran. (in Indonesian).Todd TC, TO Powers and PG Mullin. 2006. Sentinel nematodes of land-use change and restoration in tallgrass prairie. J Nematol 38: 20-27.Urzelai A, AJ Hernández and J Pastor. 2000. Biotic indices baded on soil nematode communities for assessing soil quality in terrestrial ecosystems. Sci Tot Environ 247: 253-261. van Eekeren N, H de Boer, J Bloem, C Schouten, M Rutgers, R de Goede and L Brussaard. 2009. soil biological quality of grassland fertilized with adjusted cattle manure slurries in comparison with organic and inorganic fertilizers. Biol Fertil Soils 45: 595-608.  Voroney RP. 2007. The soil habitat. In: Paul EA (ed.). Soil Microbiology, Ecology, and Biochemistry. Elsevier, Amsterdam, pp.25-49.Wardle DA, RD Bardgett, JN Klironomos, H Setälä, WH van der Putten and DH Wall. 2004. Ecological linkage between aboveground and below ground biota. Science 304: 1629-1633.Widyastuti R. 2006. Feeding rate of soil animals in different ecosystem in Pati, Indonesia. Hayati 13: 119-123.Wilke BM. 2005. Determination of chemical and physical soil properties. In: R Margisen and F Schinner (eds). Manual for Soil Analysis –Monitoring and Assessing  Soil Bioremediation. Springer-Verlag Berlin Heidelberg, pp.47-94.Winter JP and VM Behan-Pelletier. 2008. Microarthropods. In: Carter MR and Gregorich EG (eds). Soil sampling and methods of analysis. Canadian Society of Soil Science, pp. 399-414.Yadav RS, BL Yadav, BR Chhipa, SK Dhyani and M Ram. 2011. Soil biological properties under different tree based traditional agroforestry systems in a semi-arid region of Rajasthan, India. Agroforest Syst 81: 195-202. doi: 10.1007/s10457-010-9277-z.Yan S, AN Singh, S Fu, C Liao, S Wang, Y Li, Y Cui, and L Hu. 2012. A soil index for assessing soil quality. Soil Biol Biochem 47: 158-165.Zar JH. 1999. Biostatistical analysis. Prentice Hall, New Jersey. 663 pZheng D, Jr ER Hunt and SW Running. 1993. A daily soil temperature model based on air temperature and precipitation for continental applications. Clim Res 2: 183-191.Zornoza R, J Mataix-Solera, C Guerrero, V Arcenegui, J Mataix-Beneyto and I Gómez. 2008. validating the effectiveness and sensitivity of two soil quality indices based on natural forest soils under mediterranean conditions. Soil Biol Biochem 40: 2079-2087.